2010
DOI: 10.1177/0310057x1003800110
|View full text |Cite
|
Sign up to set email alerts
|

Fibreoptic Assessment of Paediatric Sized Laryngeal Mask Airways

Abstract: Laryngeal mask airways (LMA) are commonly used in paediatric anaesthesia. A well-placed LMA should provide a direct view of the vocal cords facilitating bronchoscopy or fibreoptic intubation. The aim of this audit was to assess the bronchoscopie view of the glottis obtained through an LMA with regard to its size. We prospectively assessed the position of LMAs in relation to the glottic aperture in 350 children (zero to seven years) undergoing elective fibreoptic examination of the upper and/or lower airways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…Fiberoptic views with the LMA‐U in this study are consistent with other studies using the size two LMA (14,15). Even with complete epiglottic downfolding, both devices provided adequate ventilation parameters without evidence of airway obstruction, which is consistent with previous literature (4,18–22). The lower rates of epiglottic downfolding seen with the ILA in this study may highlight a potential advantage when considering fiberoptic‐guided tracheal intubations, especially when cuffed tracheal tubes are desired (4).…”
Section: Discussionsupporting
confidence: 91%
“…Fiberoptic views with the LMA‐U in this study are consistent with other studies using the size two LMA (14,15). Even with complete epiglottic downfolding, both devices provided adequate ventilation parameters without evidence of airway obstruction, which is consistent with previous literature (4,18–22). The lower rates of epiglottic downfolding seen with the ILA in this study may highlight a potential advantage when considering fiberoptic‐guided tracheal intubations, especially when cuffed tracheal tubes are desired (4).…”
Section: Discussionsupporting
confidence: 91%
“…Any new product should also perform at least as well as a recognized ‘gold standard’. Complication rates increase with sizes 1 and 1.5 cLMA™s in the under 10 ‐kg group (12,19–21), and our results are consistent with these findings. The results of this study have anesthetic implications for diagnostic flexible bronchoscopy procedures, and fiberoptic and blind endotracheal intubation procedures (22,23) if SGAs are utilized.…”
Section: Discussionsupporting
confidence: 90%
“…(11) found 17% of patients had partial airway obstruction based on fiberoptic examination, and 2% had clinically severe airway obstruction. In a study of 350 children, von Ungern‐Sternberg (12) found good or adequate ventilation conditions in all patients, but an incomplete view of the glottis through a flexible bronchoscope occurred in up to 50% of cases with smaller single‐use SGAs being associated with poorer views. In our study, 5.5% of SGA insertions were associated with clinically severe airway obstruction that required readjustment of the SGA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, all patients had unobstructed airways. Von Ungern-Sternberg [7] showed that complete downfolding of the epiglottis over the laryngeal inlet occurred in 11% and partial downfolding in 32% of patients using a size 1.5 LMA. It appears that the use of the size 1.5 i-gel airway should be handled especially carefully because this size covers a wide body weight range, from 5 to 12 kg, which coincides with 6-month-old to 2-year-old children.…”
Section: Discussionmentioning
confidence: 99%